Dystonia and choreoathetosis presence and severity in relation to powered wheelchair mobility performance in children and youth with dyskinetic cerebral palsy. (November 2020) - Bekteshi, Saranda; Konings, Marco; Nica, Ioana Gabriela; Gakopoulos, Sotirios; Aerts, Jean-Marie; Hallez, Hans; Monbaliu, Elegast
Abstract: Introduction: Power wheelchairs (PW) with head/foot steering systems are used as an alternative to joysticks in children with severe dyskinetic cerebral palsy (DCP). Mobility training programs are unstandardized to date, and insight on dystonia, choreoathetosis, and mobility performance may lead to greater independent mobility. Objective: To map the presence and severity of dystonia and choreoathetosis during PW mobility in DCP and their relation with mobility performance. Methods: Ten participants with DCP performed four PW mobility tasks using a head/foot steering system. Dystonia and choreoathetosis in the neck and arm regions were evaluated using the Dyskinesia Impairment Mobility Scale (DIMS). PW mobility performance was assessed using time-on-task and the number of errors during performance. The Wilcoxon-signed rank test and the Spearman's correlation coefficients were used to explore differences and correlations. Results: Median levels of dystonia (83.6%) were significantly higher (p < 0.01) than median levels of choreoathetosis (34.4%). Positive significant correlations were found between the Arm Proximal DIMS and the PW mobility experience (rs= -0.92, p < 0.001), and between the Arm Distal DIMS and the number of errors (rs = 0.66, p = 0.039) during mobility performance. Conclusions: Dystonia is more present and severe during PW mobility than choreoathetosis. The hypertonic hallmark of dystonia may mask the hyperkinetic hallmark of choreoathetosis, resulting in lower median levels. Results may suggest that with an increase in driving experience, children with DCP adopt deliberate strategies to minimize the negative impact of arm overflow movements on mobility performance, however, future research with bigger sample size and additional outcome measures is strongly encouraged. Highlights: First study to map dystonia and choreoathetosis patterns during PW powered mobility. Dystonia and choreoathetosis are both present, with dystonia levels dominating. Mobility performance is positively related to the distal arm overflow movements. Mobility experience is negatively related to the proximal arm overflow movements. Powered mobility training should initially focus on the control of the head or feet.